Four microcolumn agglutination anti-human globulin cards in unexpected antibody screening results: a comparative analysis - SONG Ke; MA Chunya; FU Lihui; XIAO Pan; SHI Hongmei; YU Yang (Zhongguo shuxue zazhi)
[Objective] To analyze the detection ability of one imported and three domestic microcolumn agglutination anti-human globulin cards in unexpected antibody screening test. [Methods] A total of 104 positive samples from antibody screening test conducted at our hospital from July to September 2022 were selected. Microcolumn agglutination antiglobulin tests were performed in parallel with antibody screening tests using one imported card (A Card) and three domestic cards (B, C and D Cards ) to analyze the differences in the sensitivity, specificity and agglutination intensity scores. [Results] The sensitivity of the four anti-human globulin cards was as follows: D card 88.51% (131/148) > C card 83.22% (124/149) > B card 81.63% (120/147) > A card 80.54% (120/149); the specificity was A card 97.79% (133/136) > B card 95.65% (132/138) > D card 95.62% (131/137) > C card 93.38% (127/136); and the average agglutination intensity score (points) was D card 214.57 > C card 191.90 > A Card 179.69 > B Card 175.83, and the H value of Kruskal-Wallis test was 7.221, with no statistically significant difference (P > 0.05). Among them, C card was prone to false positives, accounting for 3.16% (9/285), and A card was prone to false negatives, accounting for 10.18% (29/285). [Conclusion] There were differences in the detection ability of anti-human globulin cards of different manufacturers, and some domestic cards have higher detection performance than imported cards. It is recommended to use anti-human globulin cards of two manufacturers routinely in clinical practice, that is, to use cards with high detection sensitivity for antibody screening tests to avoid antibody missed detection as much as possible, and to use cards with high specificity for cross-matching blood tests to avoid delays in transfusion due to false positives, which could hinder transfusion treatment.